Staphylococcus epidermidis Controls Opportunistic Pathogens in the Nose, Could It Help to Regulate SARS-CoV-2 (COVID-19) Infection? - Silvestre Ortega-Peña; Sandra Rodríguez-Martínez; Mario E. Cancino-Diaz; Juan C. Cancino-Diaz (Life, 2022)
Staphylococcus epidermidis is more abundant in the anterior nares than internal parts of the nose, but its relative abundance changes along with age; it is more abundant in adolescents than in children and adults. Various studies have shown that S. epidermidis is the guardian of the nasal cavity because it prevents the colonization and infection of respiratory pathogens (bacteria and viruses) through the secretion of antimicrobial molecules and inhibitors of biofilm formation, occupying the space of the membrane mucosa and through the stimulation of the host’s innate and adaptive immunity. There is a strong relationship between the low number of S. epidermidis in the nasal cavity and the increased risk of serious respiratory infections. The direct application of S. epidermidis into the nasal cavity could be an effective therapeutic strategy to prevent respiratory infections and to restore nasal cavity homeostasis. This review shows the mechanisms that S. epidermidis uses to eliminate respiratory pathogens from the nasal cavity, also S. epidermidis is proposed to be used as a probiotic to prevent the development of COVID-19 because S. epidermidis induces the production of interferon type I and III and decreases the expression of the entry receptors of SARS-CoV-2 (ACE2 and TMPRSS2) in the nasal epithelial cells.